2021
DOI: 10.3934/publichealth.2021023
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 among LGBTQ+ individuals living with HIV/AIDS: psycho-social challenges and care options

Abstract: Prolonged social isolation during the COVID-19 lockdown has adversely impacted the mental, social, and physical wellbeing of the global populace. Coping with mental and physical stressors amidst the global lockdown is especially strenuous for the Lesbian, Gay, Bisexual, Transgender, and more (LGBT+) community, who are frequently subjected to social stigma and minority stress. Systematic stigma and discrimination place LGBT+ individuals at higher risk for deleterious behaviors, such as substance abuse (e.g., in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
0
13
0
2
Order By: Relevance
“…The physical and social impact was enormous – death rates grew exponentially and the healthcare system was pushed to exceed capacity in the face of enormous caseloads and a virus that spread rapidly ( Emanuel et al, 2020 , Reese et al, 2020 ). As schools, clinics, social venues, and otherwise non-essential businesses shut their doors, the most vulnerable in our society including those marginally housed, those experiencing substance use and/or those with mental health issues) were even further marginalized as a result of lost services and support ( Tomar et al, 2021 , Rozanova et al, 2020 , Usher et al, 2020 , Shiau et al, 2020 , Czeisler, 2020 , Taylor et al, 2021 , Hochstatter et al, 2021a , Green et al, 2020 ). Early in the pandemic, signs of increases in substance use ( Czeisler, 2020 ) raised concerns that substance use would skyrocket ( Das et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The physical and social impact was enormous – death rates grew exponentially and the healthcare system was pushed to exceed capacity in the face of enormous caseloads and a virus that spread rapidly ( Emanuel et al, 2020 , Reese et al, 2020 ). As schools, clinics, social venues, and otherwise non-essential businesses shut their doors, the most vulnerable in our society including those marginally housed, those experiencing substance use and/or those with mental health issues) were even further marginalized as a result of lost services and support ( Tomar et al, 2021 , Rozanova et al, 2020 , Usher et al, 2020 , Shiau et al, 2020 , Czeisler, 2020 , Taylor et al, 2021 , Hochstatter et al, 2021a , Green et al, 2020 ). Early in the pandemic, signs of increases in substance use ( Czeisler, 2020 ) raised concerns that substance use would skyrocket ( Das et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, COVID-19 burden and COVID-19 risk were predictors of depression and sleep problems [ 68 ]. Lesbian, gay, bisexual, transgender, and intersex (LGTBI) people reported an elevated risk of domestic and family violence, increased social isolation, difficulties in accessing crucial HIV treatment, and gender-affirming health services [ 67 , 69 ].…”
Section: Impact Of Sars-cov-2 Pandemic In Hiv Most-at-risk Groups and Plwhmentioning
confidence: 99%
“…For years, experience of IPV has been a known correlate of HIV risk and substance use among SGM such that SGM who experience IPV are at higher risk for HIV and more likely to use substances (Buller et al, 2014). During the COVID-19 pandemic some have suggested that social confinement may impact experience of IPV and access to IPV resources during the pandemic ( Phillips et al, 2020 , Tomar et al, 2021 ). Some surveillance data has suggested increases in domestic violence service-seeking during the COVID-19 pandemic in general populations ( Pedrosa et al, 2020 ) and one study found increased experience of IPV among adult gay and bisexual men in the first three months of COVID-19 lockdown ( Stephenson et al, 2021a , Stephenson et al, 2021b ); however, no known studies have examined the impact of COVID-19 related social distancing and IPV in SGM young adult populations.…”
Section: Intimate Partner Violencementioning
confidence: 99%
“…One concern for sexually active sexual and gender minority (SGM) populations (e.g., men who have sex with men and transgender women) was the risk for COVID-19 during sexual encounters ( Sanchez et al, 2020a , Sanchez et al, 2020b ) as well as potential disruptions in the use of Pre-exposure Prophylaxis (PrEP) for the prevention of HIV transmission ( Chow et al, 2021 , Hammoud et al, 2020a , Reyniers et al, 2020 , Sanchez et al, 2020a , Sanchez et al, 2020b ). Additional concerns were increases in intimate partner violence (IPV) ( Phillips et al, 2020 , Tomar et al, 2021 ) as well as the possibility of increased substance use ( Carrico et al, 2020 ) due to social isolation and related anxiety during the pandemic. Researchers are still trying to discern the ongoing impact of the ever-evolving COVID-19 pandemic on the lives of SGM young adults.…”
Section: Introductionmentioning
confidence: 99%